2020
DOI: 10.1371/journal.ppat.1008505
|View full text |Cite
|
Sign up to set email alerts
|

Natural killer cells expanded in vivo or ex vivo with IL-15 overcomes the inherent susceptibility of CAST mice to lethal infection with orthopoxviruses

Abstract: The wild-derived inbred CAST/EiJ mouse, one of eight founder strains in the Collaborative Cross panel, is an exceptional model for studying monkeypox virus (MPXV), an emerging human pathogen, and other orthopoxviruses including vaccinia virus (VACV). Previous studies suggested that the extreme susceptibility of the CAST mouse to orthopoxviruses is due to an insufficient innate immune response. Here, we focused on the low number of natural killer (NK) cells in the naïve CAST mouse as a contributing factor to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 57 publications
0
31
0
1
Order By: Relevance
“…Out of the 38 inbreed strains of mice (32 classical inbreed strains and six wild-derived strains) screened for susceptibility to MPXV, only three (CAST/EiJ, PERA/EiJ, and MOLF/EiJ) of the wild derived strains were highly susceptible to MPXV, and all the classical inbreed strains were highly resistant to intranasal MPXV infection. CAST/EiJ (abbreviated as CAST) is the most sensitive (of the three susceptible mouse strains) to MPXV with LD 50 of 680 and 14 infectious units via intranasal and intraperitoneal infections [37][38][39][40]. CAST was also used as a model for testing efficacy of smallpox vaccines and antivirals (Dryvax and Cidofovir) against MPXV.…”
Section: Animal Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Out of the 38 inbreed strains of mice (32 classical inbreed strains and six wild-derived strains) screened for susceptibility to MPXV, only three (CAST/EiJ, PERA/EiJ, and MOLF/EiJ) of the wild derived strains were highly susceptible to MPXV, and all the classical inbreed strains were highly resistant to intranasal MPXV infection. CAST/EiJ (abbreviated as CAST) is the most sensitive (of the three susceptible mouse strains) to MPXV with LD 50 of 680 and 14 infectious units via intranasal and intraperitoneal infections [37][38][39][40]. CAST was also used as a model for testing efficacy of smallpox vaccines and antivirals (Dryvax and Cidofovir) against MPXV.…”
Section: Animal Modelsmentioning
confidence: 99%
“…Earl et al observed that CAST was highly susceptible to MPXV, and inadequate or insufficient interferon-γ response in the lung is correlated with the vulnerability of CAST mice following intranasal infection [37,38,40]. Similarly, susceptibility of CAST mice to MPXV is due to low numbers of NK cells.…”
Section: Host Immune Responses To Mpxvmentioning
confidence: 99%
“…Staining of Lymphocytes. Splenocytes from individual mice or pooled from 3-5 mice were suspended at 1.5x10 7 cells/ml in RPMI (Quality Biological) supplemented with 10% heat-inactivated FBS, 10 U/ml penicillin, 10 µg/ml streptomycin, 2 mM L-glutamine, and 2 mM HEPES as previously described(61). Splenocytes (100 µl) were mixed with 100 µl of individual peptide pools in 96-well plates and incubated at 37 o C for 1 h after which brefeldin A(Sigma Aldrich) was added and incubation continued for 4-5 h. Staining of cells was performed at 4 o C. Fc receptors were blocked with anti-CD16/32 (Clone 2.4G2, a gift from Jack Bennink, NIAID) for 30 min.…”
mentioning
confidence: 99%
“…These results, although limited, are similar to what has been observed in other studies with experimentally infected CAST mice [ 15 , 16 ]. Studies have shown CAST and other wild-derived mouse strains to be more susceptible to OPXV infection ( Monkeypox virus , Cowpox virus , Vaccinia virus ) than other classical inbred strains of mice such as BALB/c [ 15 , 16 ], potentially due to a low level of natural killer cells and a delayed interferon-γ response [ 18 , 19 ]. It remains unclear to what degree the high pathogenicity of AKMV observed in this study is due to the increased susceptibility of CAST mice to OPXVs, or to what degree their susceptibility differs from Mus musculus in nature.…”
Section: Discussionmentioning
confidence: 99%